The INFLUENCE OF LEADER MEMBER-EXCHANGE ON EMPLOYEE CREATIVITY BY MEDIATION OF CREATIVE PROCESSES ENGAGEMENT IN STAR HOTEL IN CIREBON REGENCY - Priyono, Dadang; Gunarsih, Tri; Wening, Nur (Jurnal Ekuisci, 2024)
This research aims to determine the influence of Leader Member Exchange on Employee Creativity through Creative Process Engagement as a mediating variable in Star Hotels in the Cirebon Regency Region. The study was conducted by design. Survey research on 101 employees in Star Hotels in Cirebon Regency using this type of data through primary data with the spread of questionnaires. Variabel yang digunakan yaitu Leader Member Exchange sebagai variabel independen, Creative Process Engagement sebagai variabel mediasi, dan Employee Creativity sebagai variabel dependen. The analysis method used is pls-sem with smartpls 4.0 software tools. The results showed that Leader Member Exchange and Creative Process Engagement can have a positive and significant effect on Employee Creativity in Star Hotels in Cirebon Regency. Kemudian, Leader Member Exchange dapat berpengaruh positif dan signifikan Terhadap Creative Process Engagement di Hotel Berbintang Wilayah Kabupaten Cirebon. This study also found that Leader Member Exchange can have a positive effect on Employee Creativity in Star Hotels in Cirebon Regency through Creative Process Engagement.